Space, Identity and Education A Multi Scalar Framework - Brown, Ceri.; Donnelly, Michael (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"Space is a key aspect of education but is badly neglected by researchers and policymakers. Educational institutions are ripped out of context and made to seem like placeless places. This book takes space and its relation to student identity as its main focus. It demonstrates that social justice can never be achieved through policies that ignore this relationship. Its insights and arguments are critical and crucial." - Stephen J Ball FBA, Emeritus Professor of Sociology of Education, University College London, UK "This is a very exciting book that underlines the usefulness of bringing an explicitly geographical lens to bear on educational processes. Including fascinating case studies on the informal learning space of the playground, the spaces of home learning during the pandemic, and digital space, it puts forward an original conceptual argument about how a multi-scalar approach can enhance our understanding of the relationship between education and identity." - Rachel Brooks, Professor of Sociology, University of Surrey, UK "This important and timely text provides a spatial framework - and a series of concrete, empirically-informed exemplars - for how geographers of education might work towards a more integrative approach to studying the spatialities of identity and social justice in education spaces." - Peter Kraftl, Chair in Human Geography, University of Birmingham, UK This book details an innovative multi-scalar framework to examine the intersection of spatial levels in shaping social justice issues in education. Including an examination of key dimensions such as geographic divisions (between and within countries), school design, online learning, home-schooling, and student mobility, the framework is applied to analyse the interrelation between space, identity, and education. The authors reveal how this novel integration of scales is essential for a more comprehensive and probing understanding of educational inequalities. As an example of theoretical interdisciplinarity mobilised to tackle the urgent issues of our time, the twin dimensions of space and identity, discussed at multi-scalar levels, provides an invaluable theoretical resource for scholars and students of education, sociology and geography. Ceri Brown is a Reader in Education at the University of Bath, UK. Michael Donnelly is Professor of Education and Social Policy at the University of Bath, UK.
1. An Introduction to Space, Identity, and Education -- 2. A 'Micro' Spatial Lens on Identity and Education -- 3. A 'Meso' Spatial Lens on Identity and Education -- 4. An 'Exo' Spatial Lens on Identity and Education -- 5. A 'Macro' Spatial Lens on Identity and Education -- 6. Towards a Multi-Scalar and Multi-Method Spatial Analysis of Identity and Education -- 7. Conclusion.
Keywords: Educational sociology; Social justice; Schools; Human geography; Cultural geography; Sociology of Education; Social Justice; School and Schooling; Social and Cultural Geography